Single and repeated intra‐articular injections in the tarsocrural joint with allogeneic and autologous equine bone marrow‐derived mesenchymal stem cells are safe, but did not reduce acute inflammation in an experimental interleukin‐1β model of synovitis. (14th February 2020) - Colbath, Aimée C.; Dow, Steven W.; Hopkins, Leone S.; Phillips, Jennifer N.; McIlwraith, C. Wayne; Goodrich, Laurie R.
Abstract: Background: Allogeneic and autologous bone marrow‐derived mesenchymal stem cells (BMDMSCs) have been administered in equine joints for their anti‐inflammatory effects. However, allogeneic BMDMSC offer multiple clinical and practical advantages. Therefore, it is important to determine the relative effectiveness of allogeneic vs autologous BMDMSCs. Objectives: The objective of the study was to compare the inflamed joint response to autologous vs allogeneic BMDMSCs injections, and to determine if either treatment generated an anti‐inflammatory effect. Study design: Randomised controlled study. Method: Bone marrow was harvested from eight horses. Autologous BMDMSCs and pooled allogeneic BMDMSCs were culture expanded, cryopreserved and thawed immediately prior to administration. Ten million autologous BMDMSCs were administered with 75 ng rIL‐1β into one tarsocrural joint and the contralateral tarsocrural joint received allogeneic BMDMSC plus 75 ng rIL‐1β. Repeat injections were performed with the same treatment administered into the same joint. Four additional horses received 75 ng rIL‐1β alone in a single tarsocrural joint. Clinical parameters (lameness, joint circumference and joint effusion) and synovial fluid parameters, including nucleated cell count (NCC), differential cell count, total protein (TP), prostaglandin E2 (PGE2 ) and C‐reactive protein (CRP), were measured at baseline, 6, 12, 24, 72, 168 and 336 hours post‐injection. Results: No difference was detected between autologous and allogeneic treatment groups with respect to subjective lameness, joint effusion, joint circumference, NCC, TP, differential cell count, CRP or PGE2 . Neither autologous nor allogeneic treatments resulted in an improvement in clinical or cytological parameters over that elicited by rIL‐1β alone. Main limitations: A single dose of rIL‐1β was evaluated and resulted in a severe synovitis which may have been too severe to observe a BMDMSC‐mediated effect. Conclusions: This study revealed that allogeneic and autologous BMDMSCs resulted in an equivalent clinical and cytological response. Allogeneic and autologous BMDMSCs were equally ineffective in reducing the inflammatory response from acute rIL‐1β‐induced joint inflammation in horses.